Competition and Big 6 Brand Name Reputation: Evidence from the Ontario Municipal Audit Market - BANDYOPADHYAY, SATI P.; KAO, JENNIFER L. (Contemporary Accounting Research, 2001)
The 1991 amendment to the auditor appointment requirement of section 86 of the Ontario Municipal Act removes certain barriers to entry into the Ontario municipal audit market. The purpose of this study is to provide evidence that the amendment has enhanced competition in this market. The results indicate that there is a general reduction in the real municipal audit fees compared with the pre-amendment levels, and that the market has become more contestable following the amendment. Notwithstanding the heightened competition, the Big 6 audit firms continue to command audit fee premiums over the non-Big 6 audit firms. This suggests that Big 6 audit fee premiums possibly reflect brand name reputation rather than monopoly/oligopoly rents.